ENT 530 Company Analysis : Perusahaan Makan Meru / Mohamad Zailani Sapari ... [et al.] - Sapari, Mohamad Zailani; Zulkiply, Amira Farhana; S.Ramli, Anis Najiha; Muhammad Zaini, Norshazlin Ahsikin; Mukhtar Affandi, Siti Nur Farhana (2019)
Perusahaan Makanan Meru (PMM) offers many kinds of traditional food especially bahulu. They are located at Kampung Sg Sireh Tambahan, Klang and owned by Mr Razif and her wife, Mrs Christina Latifah Binti Abdullah. There are many types of bahulu that can attract customer's attention and those who love new style of bahulu.